(untitled) (Comprehensive Journal of Science, 2026)
During the Ottoman period, Egypt witnessed the settlement of several Tunisian families who were active in trade. Their presence in Egypt had a clear impact on the economic life of the country. Egyptian historical records provide important information about the commercial activities of these families, and the researcher relied on these records as a primary source for this study. These records reveal that these families played a prominent role in driving the Egyptian market, both in terms of exports and imports.